Effect of bread improver addition on preference, volume expansion, nutritional value, and total calories of sweet bread substituted with modified cassava flour (mocaf) - Yuliani, Yuliani; Purba, Nova Solina; Musdalifah, Nuzlul; Sagita, Yupita Veby; Utarini, Christina Elvina (Journal of Tropical AgriFood, 2026)
Modified cassava flour (mocaf) can be used as an alternative to wheat flour to reduce wheat flour consumption. Previous research has shown that substituting wheat flour with mocaf to produce sweet bread with physical and sensory characteristics similar to those of sweet bread made from 100% wheat flour requires a maximum of 20%. Efforts to increase the mocaf substitution to 40% must be accompanied by product modifications, such as the addition of a bread improver, to ensure that the resulting bread remains soft and palatable. This study aimed to determine the effect of adding a bread improver on the preference, volume expansion, nutritional value, and total calories of sweet bread substituted with 40% mocaf. The study was designed using a non-factorial Completely Randomized Design. The amount of bread improver added was 0 g (control), 0.2, 0.4, 0.6, and 0.8 g. The results of the study showed that the addition of bread improvers had a significant effect (p <0.05) (based on the Duncan Multiple Range Test) on total calories, as well as water, ash, protein, and carbohydrate content, and preference for texture, outer color, and inner color of sweet bread (based on the Dunn post hoc test). There was an increase in water, ash, and protein content and a decrease in carbohydrate and total calorie content with increasing amounts of bread improver added to sweet bread, making it a healthier alternative to bread. Meanwhile, the fat content and bread volume expansion were not affected by the amount of bread improver. The panelists liked the color, aroma, texture, and taste of the sweet bread. The addition of a bread improver of 0.8 g / 100 g produced bread that could match the nutritional value and total calories of sweet bread made from 100% wheat flour (without mocaf substitution).